Preparation of Zirconium Nitride supported on SiO2 Catalyst for Vegetable Oil Conversion - Asri, Wan Ryan; Hasanudin, Hasanudin; Wijaya, Karna (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2023)
Hydrocracking of crude palm oil (CPO) to produce biofuels was conducted over zirconium nitride supported on SiO2 (SiO2/ZrN) catalyst. SiO2/ZrN was prepared by nitriding the SiO2/Zr at 600 °C for 3 hrs under NH3 gas on the cylindrical reactor. SiO2/ZrN exhibited a surface acidity of 0.7132 mmol pyridine g‒1 with a surface area of 96 m2 g‒1, forming predominant mesopores on the catalyst. EDS-mapping analysis showed that the ZrN species exhibited a highly distributed on the SiO2 surface. CPO hydrocracking was conducted at a temperature of 500 °C for 1 hr, with a CPO flow rate of 0.02 L min‒1 and H2 flow rate of 0.03 L min‒1. The study revealed that the SiO2/ZrN successfully afforded a CPO conversion up to 94.98 wt.%, a liquid yield of 50.40 wt.%, with a low residue and coke formation. This catalyst promoted high selectivity towards bio-jet up to 72.95 wt.%.